An Elephant in the Room: Tracking an Awkward Anthropology - Kazubowski-Houston, Magdalena (Anthropologica, 2018)
Drawing on trail anthropology and the notion of the through line of action, this article tracks the feeling of awkwardness I experienced in an imaginative ethnography project I conducted in collaboration with a Polish Romani woman, Randia, in an attempt to re-envision anthropology as an engaged, collaborative and interventionist practice. I follow the trail, its offshoots and connections to arrive at what I call an awkward anthropology, which entails a radical and imaginative epistemic politics. Reflecting on how working at the intersections of ethnography, performance, storytelling and fiction shifted reflexivity from the purview of the anthropologist to that of the interlocutor, I propose an imaginative and creative praxis as a starting point for reinventing anthropology.